Hypoxia-inducible factor in cancer: from pathway regulation to therapeutic opportunity - Brian M Ortmann (BMJ Oncology)
Cancer remains one of the most formidable challenges in modern medicine, due to its complex and dynamic nature, which demands innovative therapeutic approaches. One major challenge to cancer treatment is the tumour microenvironment and in particular tumour hypoxia (low oxygen levels), which contributes to tumour progression and immune evasion. At the cellular level, this is primarily governed by hypoxia-inducible factor (HIF). HIF is a transcription factor that orchestrates cellular responses to low oxygen levels, driving angiogenesis, metabolic adaptation and immune regulation. HIF’s dysregulation is frequently observed in various cancer types and correlates with increased aggressiveness, metastasis, resistance to therapy and poor patient prognosis. Consequently, understanding the cellular mechanisms underlying HIF activation and its downstream effects has become crucial to developing targeted cancer therapies for improving cancer patient outcomes and represents a key step towards precision medicine.Recent advancements in drug development have led to the emergence of HIF inhibitors, which aim to disrupt HIF-driven processes in cancer providing therapeutic benefit. Here, we provide a review of the molecular mechanisms through which HIF promotes tumour growth and resistance, emphasising the potential clinical benefits of HIF-targeted therapies. This review will discuss the challenges and opportunities associated with translating HIF inhibition into clinical practice, including ongoing clinical trials and future directions in the development of HIF-based cancer treatments.